THE EFFECT OF VARIATION IN CURRENT STRENGTH OF 90A, 100A, AND 110A IN SMAW WELDING ON THE MECHANICAL PROPERTIES OF ASTM A-36 MATERIAL - Kurniawan Nasution, Fadly Ahmad; Nasution, Ahmad Yunus; Irwan, Ade; Fransiskus Manullang, Ileando Putra (Fakultas Teknik UM Pontianak, 2024)
ASTM A-36 material is widely used in the industrial world. ASTM A-36 steel plates are selected for mechanical property and microstructure testing by applying heat, specifically welding. This study employs the Shielded Metal Arc Welding (SMAW) method with varying current strengths of 90 A, 100 A, and 110 A. The aim of these tests is to identify defects, mechanical properties, and microstructure appearance resulting from welding ASTM A-36 steel for boiler applications in palm oil mills. The tests conducted showed that the highest average tensile strength was achieved with SMAW welding at 90 A, reaching 535.29 MPa, while the lowest was at 110 A, with 428.12 MPa. The highest average hardness test value was recorded for SMAW welding at 90 A, with a hardness value of 257.3 VHN in the Base Metal area, whereas the lowest was observed in welding with 100 A current strength, measuring 193.1 VHN in the Weld Area. Visual inspection of surface welding defects using the Penetrant Test method revealed the least number of defects in SMAW welding with 90 A and 100 A currents, consisting of two types of welding defects (Hot Cracks and porosity). Based on microstructure observation, the best visual appearance was observed in SMAW welding with 100 A current strength, attributed to its denser microstructure.